The impact of robots on labour productivity: A panel data approach covering 9 industries and 12 countries - Andre Jungmittag; Annarosa Pesole (European Commission, Joint Research Centre (JRC), 2019)
Based on the expectation that the intensified use of robots contributes to the growth of labour productivity, this paper presents estimates of Cobb-Douglas production functions, using data for 12 EU countries and 9 manufacturing industries. The empirical results for the models pooling all available data confirm that stocks of robots per 1 million Euros non-ICT capital input contribute significantly to labour productivity growth in the period from 1995 to 2015. The results remain robust, when the whole observation period is split into two subsamples from 1995 to 2007 and from 2008 to 2015. Furthermore, the model is used to assess the impact of an increase of robots use on the labour productivity in each of the 9 manufacturing industries considered.
Keywords: 330; Automation; labour productivity; panel data; production function; productivitymeasurement; robots